Archiving experience: an exploration of the challenges of preserving virtual reality. (20th May 2020) - Lischer-Katz, Zack
Abstract : Purpose: This paper aims to explore the opportunities and challenges that immersive virtual reality (VR) technologies pose for archival theory and practice. Design/methodology/approach: This conceptual paper reviews research on VR adoption in information institutions and the preservation challenges of VR to identify ways in which VR has the potential to disrupt existing archival theory and practice. Findings: Existing archival approaches are found to be disrupted by the multi-layered structural characteristics of VR, the part–whole relationships between the technological elements of VR environments and the three-dimensional content they contain and the immersive, experiential nature of VR experiences. This paper argues that drawing on perspectives from phenomenology and digital materiality is helpful for addressing the preservation challenges of VR. Research limitations/implications: The findings extend conceptualizations of preservation by identifying gaps in existing preservation approaches to VR and stressing the importance of "experience" as a central element of archival practice and by emphasizing the embodied dimensions of interpreting archival records and the multiple scales of materiality that archival researchers and practitioners should consider to preserve VR. Practical implications: These findings provide guidance for digital curators and preservationists by outlining the current thinking on VR preservation and the impact of VR on digital preservation strategies. Originality/value: This paper gives new insight into VR as an emerging area of concern to digital curation and preservation and expands archival thinking with new conceptualizations that disrupt existing paradigms.